SMALL BUSINESS OF UKRAINE IN THE MIRROR OF OFFICIAL STATISTICS - Verlanov, Yurii (Public Administration and Regional Development, 2021)
The article is devoted to the peculiarities of small business development in Ukraine. The research is primarily descriptive. The purpose of the article comprises to answer two main research questions: (1) What are the features of the structure and dynamics of small business development in Ukraine? and (2) What characterizes the policy of promoting small business development in Ukraine? Quantitative analysis is mainly based on official statistics and analytical scientific publications. Attention to small business stems from modern views on its high role in economic growth. The results obtained during the analysis demonstrate several special features of the development condition. Thus, over the last almost 10 years, the number of small enterprises (SEs) has not changed, but the number of large and medium-sized enterprises (MEs) has decreased significantly. There is a change in the sectoral structure of small and medium enterprises (SMEs): a significant reduction in the number of enterprises in financial and insurance activities, in the field of temporary accommodation and catering and in construction. Against this background, the number of new ventures in health care and social assistance and micro-enterprises in the supply of electricity, gas, steam, and air conditioning is growing. In recent years, the contribution of joint ventures to employment has increased, while the role of large and small enterprises has decreased. The participation of different groups of enterprises in the formation of value added is significantly changing: the share of large enterprises is declining, and the role of SMEs is actively growing. Distinctive is the convergence of the efficiency of personnel costs for all groups of enterprises. However, large companies show the best financial results, and they are leaders in the amount of investment per employee. The formation of the regional landscape of SMEs is rather uneven. In general, Ukraine lags far behind Georgia, the leader in the Eastern Partnership countries, in terms of small business development policy assessment: the gap is mainly in public procurement, internalization, business development services, the green economy and the institutional and regulatory framework.